Effect of aqueous extract of the leaves of Baccharis trimera on the proliferation of hepatocytes after partial hepatectomy in rats - Lima,Sonia Oliveira (2017)
Abstract Purpose: To evaluate the effect of aqueous extract of Baccharis trimera leaves on the proliferative capacity of the liver after partial hepatectomy (PH) in rats. Methods: Twenty Wistar rats weighing between 300 and 450g were divided into two groups: control (HP) and test (HP100-rats that received the aqueous extract of Baccharis trimera for four days at a dose of 100 mg / kg / day). On the fifth day, animals from both groups underwent resection of 70% of the liver. Twenty-four hours later, they were sacrificed and the remnant liver was removed and prepared for studied through PCNA immunohistochemistry. Data analysis for comparison between the two groups was made through the non-parametric statistical test Mann-Whitney test. Results: In all the animals studied was found most abundant nuclear immunostaining positive hepatocytes interlobular located in regions of the liver. Quantitative analysis of PCNA-positive cells revealed positivity rate significantly higher mean (p = 0.02) in HP100 group (77.1 ± 13.6) compared to the HP group (45.8 ± 12.9). Conclusion: DAdministration of aqueous extract of the leaves of Baccharis trimera 100 mg/kg of animal has a significant positive effect on liver regeneration in rats, 24 hours after hepatectomy (70%).